Psychological Interventions for the Fear of Public Speaking: A Meta-Analysis - Ebrahimi, Omid V.; Pallesen, Ståle; Kenter, Robin M. F.; Nordgreen, Tine (Frontiers in Psychology, 2019)
Background: Fear of Public Speaking (FoPS) or public speaking anxiety is a type of social anxiety and the most commonly feared situation in the population. FoPS is disabling with negative occupational, academic and social consequences, reported by up to one third of the population. FoPS in adolescence and adulthood is associated with an increased risk of developing generalized social anxiety disorder with further impairments. Since the last review on FoPS, a significant number of randomized controlled trials (RCTs) have been conducted assessing the effects of novel interventions with innovative modes of delivery. The objective of the present meta-analysis is to examine the effects of psychological interventions for FoPS. This study further aims to assess whether differences exist between technology-assisted modes of delivery (e.g., Internet-delivered therapies) and more traditional modes of delivering treatment (e.g., face-to-face therapies). Methods: The study investigates the effects of psychological interventions for FoPS through a quantitative meta-analysis of RCTs, using a random-effects model. Results: A total of 30 RCTs with 1355 participants were included through systematic searches of PsycINFO, MEDLINE, Web of Science and Cochrane Library. The majority of the studies investigated the effects of cognitive or behavioral interventions. Nearly half of the studies used active control groups (e.g., attention placebo), whereas the other half used passive (e.g., waitlist) controls. The overall effect of psychological interventions for FoPS across 62 interventions was 0.74 (Hedges g; 95% CI: 0.61-0.87) with low to moderate heterogeneity. The effects based on self-report measures were larger compared to physiological and behavioral outcomes. Furthermore, psychological interventions for FoPS had a small to moderate effect on generalized social anxiety disorder (g = 0.35; 95% CI: 0.22-0.48). The effect of psychological interventions aimed at FoPS at follow-up was large (g = 1.11, 95% CI: 0.90-1.31) and moderate to large for generalized social anxiety (g = 0.70, 95% CI: 0.59-0.80). There were some indications of publication bias. Conclusions: Psychological interventions are effective in reducing FoPS. Interventions using technology-assisted modes of delivery are equally effective as traditional face-to-face interventions in reducing FoPS. Psychological interventions aimed at FoPS have an effect on generalized social anxiety. Implications are discussed.